A Patient Diagnosed with Li-Campeau Syndrome and Biotinidase Deficiency - Müjgan Arslan; Halil Özbaş; Şeyma Karakoç; Rüveyda Menekşe Karataş (Galenos Publishing House, 2023)
Biotinidase (BTD) enzyme deficiency is a congenital metabolic disorder with autosomal recessive inheritance. Main symptoms in its deficiency are nervous system and skin manifestations. A 15-month-old patient who was diagnosed with Li-Campeau syndrome, was also diagnosed with BTD deficiency and his clinic rapidly improved with biotin treatment. With the awareness of different clinical presentations of BTD deficiency, patients presenting with clinical symptoms raising the suspicion of this disorder must be evaluated for enzyme activity and genetic analysis must be planned. It is of great importance to keep in mind the possibility of this rare but treatable neurometabolic disorder, even in countries with neonatal screening programme and include it in differential diagnoses in order to prevent irreversible symptoms.